Negotiating Custom and Sharia: Nahdlatul Ulama’s ‘Urf and Islamic Educational Values in the Traditions of Metes Village, Sidorejo Subdistrict, Salatiga City - Moni Kalin (Lakpesdam PCNU Kota Salatiga, 2024)
This study responds to the renewed interest in local cultures in Indonesia, which may function as social cohesion and a vehicle for value transmission, yet may also be reduced to empty ceremonialism amid modernization and the politicization of identity. The customary practices of Metes Village (Sidorejo Subdistrict, Salatiga City) are analytically significant because they remain vibrant, socially binding, and institutionalized through the authority of customary custodians (locally known as jenang kutei/jenang kutai) and the operation of customary sanctions in rituals such as cuci kampong (village cleansing) and communal feasts (umbungan/hajatan), including walimah, aqiqah, and circumcision (khitan). The study addresses two questions: (1) how Metes customary norms operate as a form of social governance within a plural community, and (2) how Islamic law evaluates these customs as a medium for internalizing Islamic educational values worship (‘ibadah), creed (‘aqidah), and morality (akhlaq). Employing a qualitative socio-legal (empirical–normative) design, the research integrates library study, documentation, and field-based accounts of relevant customary practices. Data were analyzed thematically by (i) mapping Islamic educational values (worship, creed, morality) embedded in the rituals and (ii) assessing their legal standing using widely recognized criteria for the acceptance of ‘urf: social acceptability, continuity, binding force, non-contradiction with scriptural sources (nass), and orientation toward public benefit (maslahah). The findings show that Metes customs function as a living social institution that sustains order and solidarity through community consensus and the mandate of customary custodians, while simultaneously operating as a socio-religious educational space through closing prayers, the recitation of al-Barzanji, reinforcement of social ethics, and the absence of practices associated with polytheism (e.g., offerings or burning incense). Accordingly, these customs may be recognized as valid ‘urf (‘urf sahih) insofar as they remain within the boundaries of Islamic law and serve public welfare. The study recommends strengthening intergenerational transmission of customary knowledge, standardizing ritual procedures in alignment with Islamic teachings, and redesigning customary sanctions to be proportional and educational, thereby ensuring that customs continue to cultivate socio-religious literacy and character formation without producing social harm.